Moral Development of Early Childhood in Kindergarten with Tahfidz Program: Basic Correlation of Religion and Morality - Ishlah Wahdini; Ahmad Suriansyah; Novitawati Novitawati (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research began with the increasing number of parents who send their children to tahfidz schools in the hope that their children have good religious and moral behavior. In the initial observation, the researcher finds a unique behavior in one of the children who attend tahfidz PAUD. The unique behavior that appears is the calm attitude of the child than her peers and the responsibility attitude is very high on the child, the child is very obedient to the orders and prohibitions set by her parents, and much more. The purpose of this research is to to find out the description of children’s moral behavior, the factors that influence the moral behavior and the forms of moral behavior of children aged 5-6 years at tahfidz PAUD in Banjarmasin. This research uses qualitative research with the type of case study using the Miles and Huberman model. Data collection uses three methods, that is interviews, observation, and documentation. The research subjects were children from tahfidz PAUD. The results show that the moral behavior that emerge is obedient behavior and respect for parents, honesty, responsibility, fairness, respect for others, compassion, discipline, independence, tolerance, self-control, courage, courtesy and manners in actions and words. These behaviors appear differently in the two subjects. This difference is mainly influenced by family and school factors.